Cash in hand and savings decisions - Lisa Spantig (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Cash is an important means of transaction, generally assumed to be fungible. However, behavioral economics and consumer research show that 'cash in hand', physically holding on to cash and then handing it away, affects purchasing decisions. I study how cash in hand influences decisions in a different but very important domain: savings. Savings accounts are a promising tool for reducing poverty, but the use of savings accounts is often puzzlingly low. Holding on to cash that needs to be physically deposited into a savings account may increase the psychological costs of saving. This study experimentally identifies the causal effect of cash in hand on savings deposits of microfinance clients in the Philippines. In contrast to many laboratory and several field studies with similar interventions, I do not find reduced savings deposits due to cash in hand. I discuss reasons for and consequence of this surprising finding, in particular for developing economics where lots of transactions are still cash-based.
Keywords: D90; C90; G40; 330; Cash; Savings; Experiment